Visualisasi Konsep Barisan Bilangan Real - Syaiful Hadi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2014)
A sequence of real numbers ( a sequence in R) is a function defined on the set N of natural numbers whose range is contained in the set R of real numbers. The concept of sequence can be visualized as a graph of special functions with domain on the set N and range is contained in the set R. Visualization is a bridge for students who are in transition to formal thinking.